Best practices for design and implementation of human clinical trials studying dietary oils. (January 2017) - Mackay, Dylan S.; Jew, Stephanie; Jones, Peter J.H.
Abstract: Dietary oils are a significant contributor to overall energy and fatty acid intakes. Changes in the amount and/or type of dietary oils consumed have the potential to impact human health. Clinical trials represent the gold standard for testing the health impacts of such changes in dietary oils. The objective of this review is to explore best practices for clinical trials examining impacts of dietary oils including 1) pre-clinical topics such as research question generation, study design, participant population, outcome measures and intervention product selection and/or preparation; 2) clinical trial implementation topics such as recruitment, trial management, record keeping and compliance monitoring; and 3) post-clinical trial topics dealing with sample analysis and storage as well as management, publication and data access. The use of digital case report forms, and the best practices in reporting and publishing results are also addressed. In summary, properly designed and implemented clinical trials studying dietary oils produce strong scientific evidence-guiding their use.